Examine the Effects of Climate Change on Forage Quality and its Subsequent Impact on Milk Yield and Composition - Ahmad, Mukhtar; Muhammad Jamil; Saeed Ullah; Shakirullah; Ali, Mubarik (Indus Journal of Bioscience Research, 2024)
Background: Climate change is a major threat to animal productivity because it lowers the quality of fodder, which in turn lowers milk yield and changes its composition. The connection between cow and buffalo dairy output, environmental variables, and pasture quality is explored in this research. Methods: From July 2023 through June 2024, a cross-sectional study was conducted carrying 400 animals, including 200 cows and 200 buffaloes. The mineral composition, digestibility, crude protein and fiber content of the forage were evaluated to determine its quality. The analysis focused on milk production and its constituent parts, such as fat, protein, lactose, and solids-not-fat (SNF). There was a log of feed consumption habits and environmental data (rainfall, humidity, and temperature). Findings: We found a lot of variation in the nutritional composition of the forages we looked at. Berseem had the highest levels of crude protein (17.5%) and digestibility (80.2%), whereas wheat straw had the lowest. Even while buffaloes had a higher protein and fat content (6.8% and 3.4%, respectively), cows produced more milk (12.1 ± 1.8 L/day) than buffaloes (9.8 ± 1.6 L/day). There was a positive correlation between crude protein and milk protein (r = 0.72, p < 0.001), although digestibility and yield were significantly impacted by lignin and neutral detergent fiber (NDF) (p < 0.05). Dairy output was affected by changes in fodder quality and consumption habits brought about by environmental variables. Conclusion: Climate change and forage quality have a major impact on milk production and composition. Low-quality diets restricted the performance, whereas forages like berseem and maize silage, which are high in protein and easy to digest, increase output. Sustainability of dairy output in the face of changing environmental circumstances requires adaptive measures such as climate-resilient pasture systems and precision feeding.